Examination of Gastroesophageal Reflux by Transabdominal Ultrasound: Can a Slow, Trickling form of Reflux be Responsible for Reflux Esophagitis? - László Madi-Szabo; György Kocsis (Canadian Journal of Gastroenterology)
BACKGROUND: Ultrasound can visualize significant portions of the upper and lower esophagus; it is without any instrumental interference in real conditions and displays events in motion.